Pengembangan Booklet Materi Keanekaragaman Hayati Kelas X SLTA Berdasarkan Keragaman Pterygota di Taman Sains Air Sempiang Bengkulu : (Development of Biodiversity Material Booklet for Class X SLTA Based on The Diversity of Pterygota in Science Park Air Sempiang Bengkulu) - Singkam, Abdul Rahman; Wardhani, Febrina Kusuma (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
This research aims to know the result of the feasibility and readability of the booklet on biodiversity material for class X SLTA based on the diversity of pterygota in Science Park Desa Air Sempiang Bengkulu. This research is research and development (R&D) with 4D Thiagarajan (1974) model that is limited to third stage. The research subjects were material expert, media expert, practitioner and students. Data collection techniques in this research were observation, quisioners and literature review. The results of the validation of material expert obtain a percentage of 100% with very feasible criteria, 91,6% from media expert with very feasible criteria and 94,2% from expert practicioner with very feasible criteria. The result of students readability test obtained a score of 85% with very good criteria. Based on these result, the booklet can be used as a teaching material of biodiversity for class X SLTA. Key words: booklet, pteygota, biodiversity